An analysis of the requirements for the imposition of securities transfer tax with specific focus on the securities transfer tax consequences of a repurchase of uncertificated shares - Roelofse, Lean (Department of Finance and Tax, 2019)
STT is imposed on every (i) occurrence of any ‘transfer’ event (ii) of a ‘security’ (iii) that results in a change in ‘beneficial ownership’ in that ‘security’, unless that ‘transfer’ event constitutes the issue of a security or the cancellation or redemption of a security of a company that is being wound up, liquidated, deregistered or finally terminated. However, the concept of ‘beneficial ownership’ is not defined in the STT Act and the intended scope and meaning of the concepts of a ‘security’ and a ‘transfer’ event are not necessarily clear from their definitions in the STT Act. This may result in practical difficulties. This minor dissertation primarily seeks to investigate and clarify the practical scope and meaning of the requirements for the imposition of STT. In this regard, the key finding arising from the research presented in this minor dissertation is that no STT will be imposed on a transaction involving an uncertificated share in the absence of registration of that share in the transferee’s name in accordance with the requirements of the Companies Act, 2008, even if that transaction results in a ‘change in beneficial ownership’ in that share. This is due to the fact that the imposition of STT requires the transfer of a share, which will only occur upon compliance with certain procedural requirements contained in the Companies Act, 2008. This minor dissertation also seeks to apply the requirements for the imposition of STT in the context of a share repurchase and determine whether the differing views regarding the mechanics of a share repurchase result in different STT outcomes. There is currently no uniform tax treatment of a share repurchase and legal commentators and SARS have divergent views on the mechanics of a share repurchase. In particular, there is no certainty whether a repurchased share is cancelled in the shareholder’s hands due to its repurchase, or whether it is re-acquired and cancelled by the repurchasing company. In the context of the STT Act, it is therefore unclear whether a repurchase consists of a single ‘transfer’ event or two ‘transfer’ events (that can potentially result in double STT). In this regard, a further key finding is that, notwithstanding the inconsistency in views between legal commentators and SARS regarding the mechanics of a share repurchase, the requirements for the imposition of STT can be interpreted in such a way that both views result in a single STT charge on a share repurchase. However, as both interpretations result in practical anomalies, it is recommended that the mechanics and treatment of a share repurchase be clarified through definitive guidance or legislative amendments in order to provide certainty, and eliminate the perceived inconsistency, in the tax treatment of a share repurchase.